2004
DOI: 10.1017/s0022109000003045
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Regulation Fair Disclosure: Trading Costs and Information Asymmetry

Abstract: In October 2000, the Securities and Exchange Commission (SEC) passed Regulation Fair Disclosure (FD) in an effort to reduce selective disclosure of material information by firms to analysts and other investment professionals. We find that the information asymmetry reflected in trading costs at earnings announcements has declined after Regulation FD, with the decrease more pronounced for smaller and less liquid stocks. Return volatility around mandatory announcements is also lower but overall information flow i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
127
5
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(139 citation statements)
references
References 25 publications
6
127
5
1
Order By: Relevance
“…For example, 1998 includes the four one-year windows beginning between July 1997 and June 1998. 17 Eleswarapu, Thompson, and Venkataraman (2004) find that information asymmetry costs declined following the implementation of Reg FD. Our results suggest this decline was related to a decline in the frequency of information events.…”
Section: Time Series and Cross-sectional Variation In α And σ Imentioning
confidence: 99%
“…For example, 1998 includes the four one-year windows beginning between July 1997 and June 1998. 17 Eleswarapu, Thompson, and Venkataraman (2004) find that information asymmetry costs declined following the implementation of Reg FD. Our results suggest this decline was related to a decline in the frequency of information events.…”
Section: Time Series and Cross-sectional Variation In α And σ Imentioning
confidence: 99%
“…On the other hand, studies have also shown that Reg FD indeed leveled the playing field among market participants (Eleswarapu, Thompson, and Venkataraman, 2004;Bushee, Matsumoto, and Miller, 2004;Chiyachantana, Jiang, Taechapiroontong, and Wood 2004;Ke, Petroni, and Yu, 2008). For example, Chiyachantana et al (2004) document that informed trading around earnings announcements declined post-Reg FD, whereas Ke et al (2008) find a decline in abnormal trading by transient institutional investors prior to a bad news break after the introduction of the new regulation.…”
Section: Role Of Regulationmentioning
confidence: 99%
“…Empirical evidence has documented that information asymmetry declined after Reg FD was issued (Eleswarapu, Thompson, & Venkataraman, 2004;Heflin, Subramanyam, & Zhang, 2003;Eng, Ha, & Nabar, 2013). The empirical evidence about management's earnings guidance post Reg FD is mixed.…”
Section: Earnings and Regulatory Changesmentioning
confidence: 99%